Conhecimento odontológico de adultos atendidos em uma unidade de saúde da família do município de São Carlos, Brasil - Dovigo, Mara Regina Petromilli Nordi; Garcia, Patrícia Petromilli Nordi Sasso [UNESP]; Campos, Juliana Alvares Duarte Bonini [UNESP]; Dovigo, Lívia Nordi [UNESP]; Walsh, Isabel Aparecida Porcati (My University, 2011)
The Family Health Strategy is a primary care public policy that is becoming a decisive step towards the transformation of the Brazilian healthcare model. This study evaluated the dental knowledge among individuals who attended a Family-Health Unit (FHU) in the city of São Carlos, SP, Brazil. Methods: The evaluation was based on a questionnaire with 20 questions about oral health, prevention and development of dental caries and periodontal disease. The questionnaire was given to 168 individuals, over 18 years of age and both sexes, to fill out under the supervision of a trained dentist. After data collection, the answers contained in the original questionnaires were entered into a database built using the program Excel® (Microsoft Corporation, USA) and a descriptive statistical analysis was done. Results: 66.67% of the subjects reported having received information about dental caries and periodontal disease before attending the FHU, and dentists were cited as the main source of such information (60.71%). With regard to dental caries, 70.24% of the individuals stated that they knew about the subject, but the majority of answers revealed incorrect explanation of it. The multifactorial etiology (bacteria/sugar/poor hygiene) was not mentioned. A low percentage of subjects (24.40%) claimed to know what periodontal disease is, and of these, the highest percentage of responses was related to gingivitis (26.83%) and gingival bleeding (12.20%). Out of all subjects, 80.36% affirmed that oral hygiene is important, and among them, the main reasons cited were the maintenance of oral health (29.63%), to avoid diseases (16.30%) and to preserve and prevent disease (14.81%). Conclusion: Responses from the questionnaires revealed deficient dental knowledge among the individuals. To improve the understanding about this issue, the information obtained through the questionnaire can be used to develop educational programs that will focus specifically on the major deficiencies found.

O planejamento e execução das ações educativas em saúde bucal devem levar em consideração o nível de conhecimento da população sobre as principais doenças bucais, como a cárie e doença periodontal. Assim, esse estudo avaliou o conhecimento odontológico de usuários atendidos em uma Unidade de Saúde da Família (USF) em São Carlos/SP. Métodos: O instrumento de análise foi um questionário relacionado à etiologia, prevenção e evolução da cárie dental e doença periodontal, o qual foi aplicado em 168 usuários maiores de 18 anos. Os dados coletados foram armazenados em um banco de dados e a análise dos resultados foi feita de forma descritiva. Resultados: Dos indivíduos estudados, 66,67% responderam ter recebido informações sobre cuidados de saúde bucal e a principal fonte de informação foi o dentista (60,71%). Com relação ao conhecimento sobre cárie dental, a resposta mais citada esteve relacionada com perfuração, buraco e furo nos dentes (20,34%). A etiologia multifatorial (açúcares/bactérias/má higiene) não foi citada. Uma baixa porcentagem dos indivíduos (24,40%) revelou saber o que é a doença da gengiva. De todos os participantes, 80,36% responderam saber que a correta higienização bucal é importante e os principais motivos citados foram a manutenção da saúde bucal (29,63%), evitar doenças (16,30%), preservar e prevenir doenças (14,81%). Conclusões: Concluiu-se que os usuários da USF avaliada apresentam deficiente conhecimento relativo aos temas apresentados, indicando a necessidade de melhoria desse conhecimento por meio de programas educativos.
Dental knowledge among individuals from a family-health unit in São Carlos, Brazil
Keywords: Oral health; Education dental; Family health; Saúde bucal; Educação odontológica; Saúde da família